An internal focus of attention is optimal when congruent with afferent proprioceptive task information. (March 2020) - Gottwald, Vicky M.; Owen, Robin; Lawrence, Gavin P.; McNevin, Nancy
Abstract: Whilst benefits of an external focus are shown to govern several characteristics of skill execution, specificity theory indicates that sources of afferent information most useful to performance execution are typically prioritised during processing. Objectives: We investigated whether an internal focus facilitates performance when pertinent afferent information is proprioceptive in nature and congruent with attentional focus. We also considered whether the mechanisms behind attentional focus differences are attributable to planning processes or online motor control. Design: Experiments 1 and 2 adopted a randomised design, whilst experiment 3 used a repeated measures approach. Method: In Experiment 1 we investigated movement variability as a measure of planning and error correction under external and internal focus conditions in an aiming task. Experiment 2 removed visual information to increase pertinence of proprioceptive feedback for movement execution and Experiment 3 adopted a leg-extension task, where proprioceptive salience was enhanced using an ankle weight. We hypothesised that this would increase congruency between internal focus instructions and movement production. Results: Experiments 1 and 2 revealed reduced amplitude errors under an internal focus whilst Experiment 3 showed similar findings with the addition of lower EMG activity when adopting an internal focus. Movement variability findings were indicative of enhanced planning. Conclusions: When pertinence of proprioceptive information was amplified, benefits of an internal focus were more pronounced and performance was higher. Participants were better able to focus on movement characteristics to process proprioceptive feedback: something not afforded under an external focus. This raises doubts regarding the rigidity of the constrained action hypothesis.